Novel Antimicrobial Agents for Gram-Negative Pathogens - Marios Karvouniaris; Maria Panagiota Almyroudi; Mohd Hafiz Abdul-Aziz; Stijn Blot; Elisabeth Paramythiotou; Evdoxia Tsigou; Despoina Koulenti (MDPI AG, 2023)
Gram-negative bacterial resistance to antimicrobials has had an exponential increase at a global level during the last decades and represent an everyday challenge, especially for the hospital practice of our era. Concerted efforts from the researchers and the industry have recently provided several novel promising antimicrobials, resilient to various bacterial resistance mechanisms. There are new antimicrobials that became commercially available during the last five years, namely, cefiderocol, imipenem-cilastatin-relebactam, eravacycline, omadacycline, and plazomicin. Furthermore, other agents are in advanced development, having reached phase 3 clinical trials, namely, aztreonam-avibactam, cefepime-enmetazobactam, cefepime-taniborbactam, cefepime-zidebactam, sulopenem, tebipenem, and benapenem. In this present review, we critically discuss the characteristics of the above-mentioned antimicrobials, their pharmacokinetic/pharmacodynamic properties and the current clinical data.